2020
DOI: 10.1212/nxi.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine assessment of long-term cognitive and functional status in anti-leucine-rich, glioma-inactivated 1 encephalitis

Abstract: ObjectiveTo assess the feasibility of a structured telephone interview examining the long-term cognitive and functional status in anti–leucine-rich, glioma-inactivated 1 (LGI1) encephalitis.MethodsTelephone interviews were conducted with 37 patients after a median follow-up of 87 months from disease onset and 23 healthy controls matched for age and sex. Cognitive status was assessed with the telephone Mini-Mental State Examination (t-MMSE) and 3 tests exploring verbal memory, fluency, and executive function. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 32 publications
1
49
1
Order By: Relevance
“…The Abs involved are mostly LGI1, which is an anti-neuronal surface Ab, accounting for 30% ( 18 ) of LE-related Abs. LGI1 is mainly a non-malignant tumor ( 9 11 ) and thought to be responsive to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Abs involved are mostly LGI1, which is an anti-neuronal surface Ab, accounting for 30% ( 18 ) of LE-related Abs. LGI1 is mainly a non-malignant tumor ( 9 11 ) and thought to be responsive to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment is the most common manifestation. Memory disorders, especially near memory disorders, are the most prominent ( 9 11 , 19 ). Some researchers ( 19 , 20 ) have confirmed that cognitive impairment was related to the course of disease before immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations